Regional Differences in Epidemiological and Clinical Characteristics, Treatment, and Clinical Outcomes of COVID-19 in Wuhan and Remote Areas of Hubei Province - Ren, Honggang; Guo, Xingyi; Palazón-Bru, Antonio; Yang, Pengcheng; Huo, Nan; Wang, Runsheng; Sun, Yu; Hu, Qinyong; Yang, Hua; Xu, Guogang (Frontiers in Medicine, 2021)
Abstract Background: The Coronavirus disease 2019 (COVID-19) pandemic has been a major threat to global health. Regional differences in epidemiological and clinical characteristics, treatment and outcomes of patients have not yet been investigated. This study was conducted to investigate these differences among COVID-19 patients in Hubei Province, China. Methods: This retrospective cross-sectional study analysed data on 289 COVID-19 patients from designated hospitals in three regions: Urban (Wuhan Union West Hospital), Suburban areas of Wuhan (Hannan Hospital) and Enshi city, between February 8 and 20, 2020. The final date of follow-up was December14th, 2020. The outcomes were case fatality rate and epidemiological and clinical data. Results: Urban Wuhan experienced a significantly higher case fatality rate (21.5%) than suburban Wuhan (5.23%) and rural area of Enshi (3.51%). Urban Wuhan had a higher proportion of patients on mechanical ventilation (24.05%) than suburban Wuhan (0%) and rural Enshi (3.57%). Treatment with glucocorticoids was equivalent in urban and suburban Wuhan (46.84% and 45.75% respectively) and higher than Enshi (25.00%). Urban Wuhan had a higher proportion of patients with abnormal tests including liver function and serum electrolytes and a higher rate of pneumonia (p<0.01 for all). Urban Wuhan also had a higher incidence of respiratory failure, heart disease, liver disease and shock, compared with the other two regions (all p<0.05). Conclusions: Our findings revealed that there are regional differences in COVID-19. These findings provide novel insights into the distribution of appropriate resources for the prevention, control and treatment of COVID-19 for the global community. Key words: SARS-CoV-2, COVID-19, regional differences, mortality